2020
DOI: 10.1111/eci.13334
|View full text |Cite
|
Sign up to set email alerts
|

Implications of NAD+ boosters in translational medicine

Abstract: Nicotinamide adenine dinucleotide (NAD +) is an essential metabolite in energy metabolism as well as a co-substrate in biochemical reactions such as protein deacylation, protein ADP-ribosylation and cyclic ADP-ribose synthesis mediated by sirtuins, poly (ADP-ribose) polymerases (PARPs) and CD38. In eukaryotic cells, NAD + is synthesized through three distinct pathways, which offer different strategies to modulate the bioavailability of NAD +. The therapeutic potential of dietarily available NAD + boosters pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 109 publications
(145 reference statements)
0
23
0
Order By: Relevance
“…A Parp mutation improves mitochondrial function and restores neuronal health in Aβ-Arc-expressing flies The coenzyme NAD + is not only essential for energy metabolism but also acts as a co-substrate in biochemical reactions such as protein ADP-ribosylation (PAR), catalysed by PARPs, reviewed in [16]. We have previously shown that mitochondrial dysfunction in pink1 or parkin mutant flies, two genes implicated in Parkinson's disease, causes an increase in PAR levels.…”
Section: Identification Of a Metabolic Signature Linked To Nicotinate And Nam Metabolism In Flies Expressing Toxic Aβmentioning
confidence: 99%
“…A Parp mutation improves mitochondrial function and restores neuronal health in Aβ-Arc-expressing flies The coenzyme NAD + is not only essential for energy metabolism but also acts as a co-substrate in biochemical reactions such as protein ADP-ribosylation (PAR), catalysed by PARPs, reviewed in [16]. We have previously shown that mitochondrial dysfunction in pink1 or parkin mutant flies, two genes implicated in Parkinson's disease, causes an increase in PAR levels.…”
Section: Identification Of a Metabolic Signature Linked To Nicotinate And Nam Metabolism In Flies Expressing Toxic Aβmentioning
confidence: 99%
“…In conclusion, the present study furthers our understanding of the complex network of events that regulate iNAD+ content. Finally, it suggests that the therapeutic potential of the different NAD+-boosting strategies ( 67 ) might be significantly reduced in those tissues in which the NAD+-resetting response is functionally relevant. Of course, NAD+-supplementation strategies may still be of therapeutic relevance in conditions of iNAD+ deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Given the vital role of NAD in many cellular processes, it is not surprising that NAD + levels were shown to be decreased in aged individuals and supplementation with NAD + precursors was proven to ameliorate age-related disorders, including neurodegenerative diseases [74][75][76]. In line with that, the function of NAD + -dependent enzymes, such as sirtuins and ARTs, was shown to change upon aging [77].…”
Section: Nad + Quantificationmentioning
confidence: 91%